Individual competencies for self-managing team performance: a systematic literature review - Doblinger, Maria (Small group research, 2022)
Self-managing teams are popular but they can only benefit team performance if their members are competent to navigate within self-managing systems. Based on a systematic literature search on self-managing, self-directing, and self-leading teams, we reviewed 84 studies related to KSAOs and traits in self-managing teams. Grounded on existing models of team effectiveness and individual KSAOs, we integrated all findings into one KSAO model and showed the relations of single KSAOs with team performance. The results resembled other KSAO frameworks but were more comprehensive and provided practical application and future research guidance, for example, studying team compositions of individual KSAOs.
First published online August 24, 2021
Gesehen am 06.02.2023